OPTIMALISASI OPERASIONAL TOWER CRANE PADA PEKERJAAN ARSITEKTURAL PELAKSANAAN KONSTRUKSI GEDUNG BERTINGKAT TINGGI 168 METER (PROYEK HOLLAND VILLAGE JAKARTA) - Suharianto .; Syahril Taufik (Institut Sains dan Teknologi Nasional, 2022)
ABSTRACT This thesis discusses the operation of tower cranes in high-rise building construction. In the implementation of high-rise building projects, tower crane vertical transportation operations are very decisive as the most important means for lifting and transporting material supply on each working floor. The Holland Village Jakarta project is experiencing obstacles to the efficiency of construction completion which has not been in accordance with duration of the time schedule set. For this reason, an analysis of the optimization of tower crane operations is carried out in terms of human resource factors, material resources, method resources, and environmental conditions. And also carried out an analysis of risk management so as to achieve optimization of tower crane vertical transportation operations. The approach taken is to use risk management based on the dominant risk response analysis to make relevant strategic decisions. The configuration of 3 tower cranes is carried out by analyzing hierarchical decisions using the Analytical Hierarchy Process (AHP) method with the selection of the best alternative configuration. The results of the hierarchy of dominant response criteria in sequence, namely: economic/cost criteria, time efficiency, ease of implementation, and criteria for transportation of architectural materials. The alternative configuration of the KTC-3 tower crane is effective as a weight value of 33.78% with a change in position configuration from the existing tower configuration. The duration of construction can be optimized by 10 days in 5.5%. Keywords: tower crane, risk response, AHP, configuration, duration